2010
DOI: 10.3109/02841861003631487
|View full text |Cite
|
Sign up to set email alerts
|

From cell population models to tumor control probability: Including cell cycle effects

Abstract: The cell cycle can be understood as the sequestration of cells in the quiescent compartment, where they are less sensitive to radiation. We suggest that our model can be used in combination with synchronization methods to optimize treatment timing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 32 publications
0
27
0
2
Order By: Relevance
“…Note that since active cells are more radiosensitive, we have h A ( t ) >  h Q ( t ). The original model of Dawson and Hillen have been taken and extended to describe more complex systems or models with more compartments [25, 32, 59, 68]. Analysis of Dawson and Hillen active-quiescent radiation model and its comparison to LQ model confirms that a larger α / β ratio relates to a fast cell cycle and indicates the presence of a significant quiescent compartment, while a smaller ratio is associated with a slow cell cycle [23].…”
Section: Modeling and Optimization In Radiotherapymentioning
confidence: 99%
“…Note that since active cells are more radiosensitive, we have h A ( t ) >  h Q ( t ). The original model of Dawson and Hillen have been taken and extended to describe more complex systems or models with more compartments [25, 32, 59, 68]. Analysis of Dawson and Hillen active-quiescent radiation model and its comparison to LQ model confirms that a larger α / β ratio relates to a fast cell cycle and indicates the presence of a significant quiescent compartment, while a smaller ratio is associated with a slow cell cycle [23].…”
Section: Modeling and Optimization In Radiotherapymentioning
confidence: 99%
“…Naturally, such analysis can be extended to weekends off schedules. Table 2 lists typical prostate cancer parameters used in our simulations: the initial number of tumour cells (active and quiescent ones), the net mean rates for mitosis   0 0 N  and migration  (both ones discounted   from natural death rates in the active and quiescent compartments, respectively, as in reference [3]) and the parameters i  and i  related to the radiosensitivities in the compartment. The chosen parameters are the same ones as used by Gong et al [6] when studying the DH two-compartment model.…”
Section: Maxmentioning
confidence: 99%
“…Prostate tumours have different radiosensitivities [20] (and thus react differently to the treatment) since cancer cells properties differ from one tumour to another and even in the same tumour. Nevertheless, cells in the same compartment of the model are considered to be identical [3].…”
Section: Maxmentioning
confidence: 99%
See 1 more Smart Citation
“…The mathematical framework comes directly from ecological applications, but the interpretations, and some of the details are specific to cancer modelling. This direction of research has blossomed in beautiful theories on brith-death processes and branching processes, which are able to include cell cycle dynamics and differential radiosensitivities depending on the cell cycle state (see [22,25,26,31,43,61,66]). In a recent PhD thesis, Gong [21] included cancer stem cells into the TCP models and she confirmed that it is critical to control the stem cells for treatment to be successful.…”
Section: Tumor Control and Treatmentmentioning
confidence: 99%